Didactic Design for Overcoming Learning Obstacles in Mathematics of Junior High School Students - Lisa Astriani; Abdul Mujib; Firmansyah (PT Inovasi Pratama Internasional, 2022)
This study aims to formulate an alternative design for learning the concept of flat-sided wake-up space against the background of didactic situations and learning obstacles experienced by students. This type of research is a DDR (Didactical Design Research) research. The didactic design was developed through three stages, namely: first, compiling an initial design based on student barriers that had previously been identified, secondly analyzing metapedadydactics carried out during learning, and thirdly, retrospective analysis carried out by identifying learning obstacles and compiling learning designs. This research was conducted at Mts Al Washliyah Tanjung Morawa class VIII with 35 students. The results of this study indicate that there are several learning obstacles that occur to students, namely errors in the concept of flat side space, errors in multiplication, and also errors in answering questions whose context is different from the example questions given. Based on the identification results that have been analyzed, one of the alternative solutions is to develop alternative solutions to the concept of flat side space in order to minimize barriers to learning.